THE INFLUENCE OF INFORMATION CONTENT ON THE EMOTIONAL STABILITY OF STUDENTS OF VOCATIONAL SCHOOLS UNDER THE CONDITIONS OF MARITAL STATE - Khomenko-Semenova, Lesia; Prokhorenko, Yana (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2022)
The article analyzes the influence of information content on the emotional stability of students in the conditions of martial law. The main elements of the influence of the information space, in particular news, on the emotional state of higher education students are considered and analyzed. The purpose of the article is to determine the attitude of students to information content in the conditions of martial law; to investigate the impact of news on the emotional and physical state of students of higher education institutions. The results of the study showed that the ways of forming stress resistance at student age include factors that shape students’ stress resistance by choosing successful types of coping behavior and correcting the levels of anxiety: the ability to solve problems and a positive vision of the future; approval of one’s actions by others; individual psychological characteristics of a person (self-confidence, activity, optimism); satisfaction with the chosen profession and a positive emotional background. The formation of stress resistance in the student age is possible thanks to the implementation of the method of psychological training, where exercises should be used that contribute to the self-regulation of the student’s condition, activation of mental functions, motivate students to develop certain components of the psyche, etc. Conclusions. Based on scientific works on stress resistance, it is possible to single out the psychological features of the stress resistance of higher education students: psychodynamic properties (activity, rigidity, emotional excitability, reaction rate); willpower (endurance, determination, perseverance, self-control, initiative, independence, responsibility, energy); features of self-regulation of behavior (planning, modeling, assessment of results, flexibility, general level of self-regulation of behavior); motivation (motivation of the desire for success). Summarizing the results of the author’s questionnaire to determine the attitude of students to the news in the conditions of martial law and the impact of news on the emotional and physical state of students of higher education institutions in the conditions of martial law, it was found that for most students, viewing the news causes negative and disturbing emotions, internal discomfort in the body, reduces motivation to activities, concentration on studies, work